2019
DOI: 10.1055/s-0039-1696732
|View full text |Cite
|
Sign up to set email alerts
|

Oncologists' Perceptions of a Digital Tool to Improve Cancer Survivors' Cardiovascular Health

Abstract: Background Cardiovascular (CV) disease continues to be a leading cause of morbidity and mortality with higher rates among cancer survivors than in the general population. Objective This study was aimed to understand oncology providers' attitudes toward a digital CV health tool, delivered via a tablet, to promote CV health in cancer survivors. Methods Using qualitative methods, 14 oncologists, from community and academic practice sites, were interviewed while they used the tool. Interviews w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 68 publications
(73 reference statements)
0
11
0
Order By: Relevance
“…Many studies focused on creating and evaluating mobile apps, typically aimed at addressing the needs of patients and consumers. These mobile apps focused on a variety of chronic diseases such as diabetes and hypertension [ 63 , 122 ], cardiovascular health [ 30 , 58 , 121 ], cancer care [ 58 , 127 ], mental health [ 13 , 23 , 25 , 57 , 110 ], seizure management [ 57 ], bladder monitoring [ 56 ], tuberculosis treatment [ 15 ], and parental education [ 40 , 41 ]. A small number of studies focused on telehealth [ 10 , 14 , 140 ] and personal health records or patient portals [ 38 , 109 , 141 ].…”
Section: Resultsmentioning
confidence: 99%
“…Many studies focused on creating and evaluating mobile apps, typically aimed at addressing the needs of patients and consumers. These mobile apps focused on a variety of chronic diseases such as diabetes and hypertension [ 63 , 122 ], cardiovascular health [ 30 , 58 , 121 ], cancer care [ 58 , 127 ], mental health [ 13 , 23 , 25 , 57 , 110 ], seizure management [ 57 ], bladder monitoring [ 56 ], tuberculosis treatment [ 15 ], and parental education [ 40 , 41 ]. A small number of studies focused on telehealth [ 10 , 14 , 140 ] and personal health records or patient portals [ 38 , 109 , 141 ].…”
Section: Resultsmentioning
confidence: 99%
“…Despite Institute of Medicine recommendations for adequate prevention efforts and care coordination for cancer survivors [ 13 - 15 ], cardiovascular risk continues to be undertreated in this population [ 16 , 17 ]. The majority of National Cancer Institute Community Oncology Research Program oncologists we interviewed (11 of 14) in a pilot study [ 18 ] reported cardiovascular health discussions to be “somewhat” or “very” important. Yet in general survivorship settings, few referrals for cardiovascular care are made by oncologists to primary care providers and cardiologists for guideline-driven follow-up care [ 11 , 16 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Use of SPHERE resulted in improved BMI and diabetes status in the interventional primary care clinic but not the control clinic [ 31 ]. We refined this tool based upon feedback received from qualitative interviews with oncologists [ 18 ] and added information about receipt of potentially cardiotoxic cancer treatments. For this study, we evaluated the acceptability of the new Automated Heart-Health Assessment tool (AH-HA, Figure 1 ) among oncology providers and the Vigor-Us mobile app ( Figure 1 ) among breast cancer survivors.…”
Section: Introductionmentioning
confidence: 99%
“…Claims data reveal that only 31–39% of breast cancer survivors received cholesterol screening, significantly fewer than matched women without breast cancer [ 7 ]. Ninety percent of oncologists we surveyed reported cardiovascular health (CVH) discussions to be “somewhat” or “very” important; however, 58% “rarely” or “sometimes” discuss CVH with their patients [ 8 ]. As a result, oncologists make few referrals for cardiovascular (CV) care to primary care and cardiology for guideline-driven follow-up care [ [9] , [10] , [11] , [12] ].…”
Section: Introductionmentioning
confidence: 99%